MENINGKATKAN MOTORIK HALUS ANAK USIA 4- 5 TAHUN MELALUI KEGIATAN MENGGUNTING BENTUK GEOMETRI DI RA ROUDLOTUL ULUM ARROYAN - Kholifah, Kholifah; Warih Windasari, Indriana (LPPM IAD Probolinggo, 2024)
he aim of the assessment is to see the level of children's fine motor skills, and how to improve children's fine motor skills by cutting out geometric shapes at RA ROUDLOTUL ULUM ARROYA. The study is a class room [PTK] assessment which is carried out in two cycles consisting of the design, implementation levels. , exploration, and description. The research results show the level of children's fine motor skills during teaching and learning activities at RA ROUDLOTUL ULUM ARROYAN. Before the researchers implemented the geometric shape cutting activity, 10 children [90%] had not yet developed and 1 child [9%] was starting to develop. results of the assessment of improving children's fine motor skills before the activity of cutting out geometric shapes [pre] cycle. Of 5 children [54%] with very low criteria. and in cycle 1 there was an increase to 90% with a very high increase. This shows that the actions carried out through the activity of cutting out geometric shapes can improve children's fine motor skills at RA ROUDLOTUL ULUM ARROYAN for the 2023-2024 academic year. Keywords : Cutting, Fine Motor Skills, Geometric Shapes